The New North in Canadian History and Historiography - Coates, Kenneth (History compass, 2008)
This article reviews the current state of the historiography of the Canadian North, connecting scholarly writing on the region to the rapid and profound developments that have occurred in the North in recent years. It summarizes the priorities and imperatives of post-Second World War historical writing on the North but looks more specifically at developments in the past two decades. The rapid growth of Indigenous-focused and North-centred scholarship is considered in detail, with particular emphasis placed on the manner in which academics have collaborated with Aboriginal peoples on the advancement of historical understanding. Despite the growth in the number, quality and diversity of historical works on the North, this article argues that the national historical profession continues to largely ignore northern developments and has yet to integrate the region into the national narrative. The article concludes by reviewing the prospects for further development in the field, suggesting that significant challenges lie ahead, including a growing disconnect between southern and northern historical work, the rising costs of working closely with Indigenous communities, and the general decline of regional history in Canada.